Comparative Study on Extraction of Humic Acid from Pakistani Coal Samples by Oxidizing the Samples with Hydrogen Peroxide - Muhammad Asif (ASEAN Journal of Science and Engineering, 2022)
Humic Acid is soil conditioning agent, which is used for improving the soil chemistry, plant root growth and related metabolism. Pakistan is an agricultural country and about 70% of population is directly or indirectly linked to the agricultural sector. Coal is considered one of the most appropriate raw materials for humic acid. The yield of extracted humic acid from coal is inversely proportional to the rank of coal. Since, majority of Pakistani coals are of low rank, extraction of humic acid from indigenous coal may be one of the non-fuels uses of coal. Three different coal sample from Thar, Dukki and Chamalong coalfields were treated with 3% H2O2 solution for determining the impact of oxidation on humic acid yield. The yield of humic acid from H2O2 treated samples were as follows; 2.5% for Chamalong coal sample, 16.5% from Dukki, and 35% from Thar coal sample. Thar coal sample, being the lowest in rank among all experimented coal samples, yielded higher fraction of humic acid.